2017
DOI: 10.1007/s11356-017-8629-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal accumulation in some aquatic insects (Coleoptera: Hydrophilidae) and tissues of Chondrostoma regium (Heckel, 1843) relevant to their concentration in water and sediments from Karasu River, Erzurum, Turkey

Abstract: The objectives of this research were to determine and compare the heavy element concentrations in two study areas in Erzurum, Turkey (Aşkale and Dumlu sites). Assessment of some heavy elements in sediment, water, fish (Chondrostoma regium) tissues, and some aquatic insects (Coleoptera: Hydrophilidae) were carried out in June to August 2014. Heavy element levels in aquatic insect samples and their associated water and sediment were analyzed by energy dispersive X-ray fluorescence (EDXRF) spectrometer. Fish tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The higher level of Fe and Zn in Devario regina , Channa striatus might be originated form the consumption of water bugs and insects because such aquatic insects are sensitive to both biotic and abiotic factors and can accumulate trace metals from sediments and food. A recent study has shown that such bugs can accumulate a higher amount of Fe, Zn and Cu and solubility of Fe from insects which is even higher than beef [ 62 , 63 ]. Furthermore, from Table 6 it can be elucidated that both Devario regina and Barbonymus schwanenfeldii contain a higher amount of Pb contents because both species take aquatic plants parts as their food.…”
Section: Resultsmentioning
confidence: 99%
“…The higher level of Fe and Zn in Devario regina , Channa striatus might be originated form the consumption of water bugs and insects because such aquatic insects are sensitive to both biotic and abiotic factors and can accumulate trace metals from sediments and food. A recent study has shown that such bugs can accumulate a higher amount of Fe, Zn and Cu and solubility of Fe from insects which is even higher than beef [ 62 , 63 ]. Furthermore, from Table 6 it can be elucidated that both Devario regina and Barbonymus schwanenfeldii contain a higher amount of Pb contents because both species take aquatic plants parts as their food.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the abundant content of titanium in the Earth’s crust, water contamination by abnormal content of titanium might also affect human health. Titanium has been found in river water, and thus accumulated in aquatic insects [ 85 ]. Therefore, its possible impacts on the food chain and the agricultural damage must be considered.…”
Section: Toxicity Of Titanium and Its Alloysmentioning
confidence: 99%
“…The results of the analyses are given in Table 2. Heavy element analyses were done as described in Aydoğan et al (2017;. Firstly, the samples were dried in an oven at 80°C during 36 h, then pulverized and applied five-ton pressure to make 13 mm diameter tablets of each sample.…”
Section: Edxrf Analysismentioning
confidence: 99%
“…If the limit is exceeded, environmental heavy element pollution begins when element concentrations exceed the self-renewal capacity of nature. In literature there are numerous studies about heavy elements in urban areas which indicate that they are persistent, spreading widely in the environment, pose threat to natural components and human health (Aydoğan et al, 2017;Ye et al, 2018). The term "heavy metal" was searched on the Web of Science (WOS) publication in number 5 360, 64 575 and 88 173 records in the year 1970-1990, 1990-2010 and 2010-2019 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation